Malacological survey of potentially contaminated waters at outbreaks of transmission of schistosomiasis mansoni in the city of Betim, Minas Gerais, Brazil - Vargas Garcia, Ana Paula; dos Santos, Vânia Cristina; Santos Carvalho, Omar; Lima Caldeira, Roberta; Lafetá Furtado Mendonça, Cristiane (Revista de Patologia Tropical / Journal of Tropical Pathology, 2023)
Schistosoma mansoni, which causes schistosomiasis mansoni, has humans as the primary definitive host and the mollusks Biomphalaria glabrata, B. straminea and B. tenagophila as intermediate hosts. The goal of this research was to undertake a malacological survey on watercourses in the city of Betim, using the data provided by the city´sHealth´s Department. The mollusks were collected from pre-selected sites, examined for the presence of cercariae and taxonomically-identified, by morphological and molecular techniques for species. 168 mollusks were collected in eight collection sites. The species found were B. glabrata, B. straminea and B. tenagophila. Four B. glabrata from one of the sites were positive for S. mansoni. These results and the presence of intermediate hosts throughout the region studied, even if not found to be infected, is of epidemiological importance and suggests that the health authorities from the city of Betim should implement disease control measures. KEY WORDS: public health; bioindicators; malacology; malacofauna; distribution ecology; vector expansion.